An analysis of high-frequency cryptocurrencies prices dynamics using permutation-information-theory quantifiers - Fernández Bariviera, Aurelio (2018)
This paper discusses the dynamics of intraday prices of 12 cryptocurrencies during the past months´ boom and bust. The importance of this study lies in the extended coverage of the cryptoworld, accounting for more than 90% of the total daily turnover. By using the complexity-entropy causality plane, we could discriminate three different dynamics in the data set. Whereas most of the cryptocurrencies follow a similar pattern, there are two currencies (ETC and ETH) that exhibit a more persistent stochastic dynamics, and two other currencies (DASH and XEM) whose behavior is closer to a random walk. Consequently, similar financial assets, using blockchain technology, are differentiated by market participants.